OPTIMALISASI LEMBAGA PEMBIAYAAN MODAL VENTURA SEBAGAI ALTERNATIF PEMBIAYAAN BAGI USAHA MIKRO, KECIL DAN MENENGAH DALAM RANGKA MEWUJUDKAN PEMBANGUNAN EKONOMI NASIONAL - Setiady, Tri; Hanafiah, Yohan (Universitas Wiralodra, 2023)
The Government's policy in regulating venture capital financing services is related to the aim of its establishment, namely as an alternative financing to divert financing from banking to venture capital for micro, small and medium enterprises (MSMEs) which are usually difficult to obtain financing from banks. Because in general small entrepreneurs do not have management, do not have capital and do not have human resources to run their business. One of the government's efforts to provide assistance to small entrepreneurs is by providing alternative financing through financing institutions, one of which is called Venture Capital.